Optimization of effective composting process of oil palm industrial waste by lignocellulolytic fungi - Mohammad, Noor; Alam, Md Zahangir; Kabashi, Nassereldeen A. (Springer Japan, 2014)
A batch study was carried out to optimize four process parameters such as particle size (1–5 mm), pH (4–7), mix ratio (1:1–1:3) of substrates (empty fruit bunch, EFB and palm oil mill efﬂuent, POME) and supplementary nutrient as non-food cassava starch (0–2 % w/w). The parameters were evaluated based on the results of electrical conductivity, protein content, organic matter and C/N ratio for an effective composting process. The total period of composting was 35–40 days, a shorter time than the tra-ditional composting process ([60 days). The results showed that the 2-mm particle size of EFB was most suitable to grow microbes, gave the highest protein of 85 g kg-1 and degraded fastest (lowest C/N ratio of 16). Substrate ratio 1:3 (EFB and POME) and pH 5.0 were found to be favorable for mature compost through faster degradation (ﬁnal C/N ratio almost 17) and microbial growth (around 130 g kg-1 of protein). Moreover, non-food cassava used as supplementary nutrients for initial microbial growth was evaluated and did not signiﬁcantly affect the results